Use of drone with digital photographic machine embedded for determination of leaf cover - Michels, Roger Nabeyama; Bertozzi, Janksyn; Dal Bosco, Tatiane Cristina; de Aguiar e Silva, Marcelo Augusto; Gnoatto, Estor; Endo Soares, Cinthia Harumi (Revista Agrogeoambiental, 2019)
The normalized difference vegetation index (NDVI) obtained via radiometer is important to determine the physiological state of plant, being a promising tool for decision making as to the best time for the application of agricultural pesticides, to analyze the threshold of economic damage. The use of drones with digital camera embedded in agriculture is in broad expansion. Through digital images analyzed in computer programs and correlated with NDVI it is possible to determine the leaf cover in plants. The aim of this study was to confirm the use of digital images at 30 m in height to determine the leaf cover, correlating them with NDVI values obtained on the ground. Therefore, 30 m height photos were taken with the help of a drone and three stages of maize development (N4, N8 and R1), which were considered as treatments; afterwards, the images were analyzed in software to survey the leaf cover. The NDVI data were obtained in the same areas at a height of 0.5 m from the crop canopy, and it were submitted to the Scott Knott Test at 5 % significance and Pearson correlation. There was no statistical difference between methods and the Pearson correlation coefficient value (0,952) confirms strong evidence for correlation between the two methods. Thus, it can be concluded that the use of drone with embedded digital camera has promising use for the determination of leaf cover in maize.